Testing and evaluation of agricultural machinery - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Testing and evaluation of agricultural machinery and equipment: principles and practices by D W Smith, B G Sims and D H O'Neill 1994 272pp FAO Agricultural Services Bulletin 110 ISBN 92 5 103458 3 FAO Publications Dept, FAO, Via delle Terme di Car